Greenhouse gas emissions from global cities under SSP/RCP scenarios, 1990 to 2100. (March 2022) - Gurney, Kevin R.; Kılkış, Şiir; Seto, Karen C.; Lwasa, Shuaib; Moran, Daniel; Riahi, Keywan; Keller, Meredith; Rayner, Peter; Luqman, Muhammed
Highlights: Urban areas have accounted for the majority of global GHG emissions in 2015 (61.8%). Urban emission scenarios are established within seven pathway combinations to 2100. The scenarios have implications for urban mitigation and climate neutrality targets. Two regions can represent up to 73.3% of cumulative consumption-based urban emissions during 2020–2100. The study provides a new approach for quantifying urban emissions within scenarios. Abstract: Projections of greenhouse gas (GHG) emissions are critical to enable a better understanding and anticipation of future climate change under different socio-economic conditions and mitigation strategies. The climate projections and scenarios assessed by the Intergovernmental Panel on Climate Change, following the Shared Socioeconomic Pathway (SSP)-Representative Concentration Pathway (RCP) framework, have provided a rich understanding of the constraints and opportunities for policy action. However, the current emissions scenarios lack an explicit treatment of urban emissions within the global context. Given the pace and scale of urbanization, with global urban populations expected to increase from about 4.4 billion today to about 7 billion by 2050, there is an urgent need to fill this knowledge gap. Here, we estimate the share of global GHG emissions driven by urban areas from 1990 to 2100 based on the SSP-RCP framework. The urban consumption-based GHG emissions are presented in five regional aggregates and based on a combination of the urban population share, 2015 urban per capita CO2 eq carbon footprint, SSP-based national CO2 eq emissions, and recent analysis of urban per capita CO2 eq trends. We find that urban areas account for the majority of global GHG emissions in 2015 (61.8%). Moreover, the urban share of global GHG emissions progressively increases into the future, exceeding 80% in some scenarios by the end of the century. The combined urban areas in Asia and Developing Pacific, and Developed Countries account for 65.0% to 73.3% of cumulative urban consumption-based emissions between 2020 and 2100 across the scenarios. Given these dominant roles, we describe the implications for potential urban mitigation in each of the scenario narratives in order to meet the goal of climate neutrality within this century.